Measurements of labile Cd, Cu, Ni, Pb, and Zn levels at a northeastern Brazilian coastal area under the influence of oil production with diffusive gradients in thin films technique (DGT) - Souza, Joao M. de; Menegario, Amauri Antonio; Araujo Junior, Marcus A. G. de; Francioni, Eleine (Elsevier B.V., 2014)
In this work, the ability of the diffusive gradients in thin films technique (DGT) was evaluated for monitoring the concentrations, and estimating the availability, of metals at a northeastern Brazilian coastal area under the influence of oil production. Three sites with an average distance between 0 m (EM-1), 100 m (EM-2), and 1000 m (EM-3) of a submarine outfall-I (Guamare RN, Brazil) and another site (GA-1) with an average distance of 12000 m east of Outfall I, near the city of Galinhos, were studied. DGT units were deployed at the same sites in three campaigns from July, 2010 to June, 2011.Effects on the accuracy of analytical results regarding the deployment time, gel porosity, and thickness were evaluated. There was no difference between the measurements obtained with two sets of DGT devices, those assembled with open or restrictive pore gel, respectively, showing that organic metallic species are not present near the submarine outlet. After 21 day deployments in a region (near Submarine Outfall I) that receives produced waters that have been treated, there was evidence of biofilm formation on DGT membranes. However, it was demonstrated that the biofilm interference with DGT measurements was negligible.Data found in this work show that total concentrations of Cd, Cu, Pb, Ni, and Zn in seawater samples collected at sites GA-1 and EM-1 in two campaigns were below 033, 1.67, 0.47, 0.70, 2.86 ng mL(-1) respectively. For the first time, labile levels of Cd, Cu, Pb, Ni, and Zn in an area under the influence of oil production were determined. DGT measurements allowed the verification of the effects of temporal variation on levels of Zn and Ni. There were no effects of spatial variations on levels of Cd, Cu, Ni, Pb, and Zn at the four studied sites, suggesting no contamination of these metals at the northeastern Brazilian coastal area investigated in this work. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Passive sampler; Oil refinery; Oil production; Metal; Labile